UPAYA HUKUM BANK UNTUK MENDAPATKAN KEMBALI UANG YANG DIPINJAMKANNYA AKIBAT KREDIT MACET KARENA KELALAIAN PEKERJA BANK BAGIAN APPRAISAL - Hastika, Adrian Richkiel (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
The Bank is one of the parties that supports the achievement of community welfare improvement. This is evident from one of the bank's authority to collect public funds in the form of savings which is then channeled to other parties in the form of credit. Funding in the form of credit must be accompanied by prudential banking principles because it is responsible for the welfare of the public. Typically, in giving credit, the bank requests a guarantee that is first assessed by an appraisal.